Analisis Performa Kelincahan dan Daya Ledak Otot Tungkai Berdasarkan Variasi Lengkung Telapak Kaki pada Pemain Sepak Bola Level Daerah - Resmana, Dadan; Ganeswara, Raisa; Gani, Abdul; Kridasuwarso, Bambang; Rihatno, Taufik; Samsudin, Samsudin; Ginanjar, Shela (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
The arch of the foot is a biomechanical structural element that can affect the physical performance of athletes in sports that require dynamic movements such as soccer. The arch of the foot, both normal and flat, contributes to the efficiency of movement and load distribution when running, jumping, and changing direction suddenly. Therefore, this study aims to analyze the differences in agility performance and vertical leg muscle explosive power in regional-level soccer players based on variations in the shape of the arch of the foot, namely normal and flat. The method used is an observational study involving regional-level soccer players aged 19–22 years who have participated in regional-level competitions. Agility measurements were carried out using an 8×5 meter back and forth running test, while vertical jumping ability was assessed through a vertical jump test using the Vertec tool. The results of the study with the t-test showed that there was no significant difference between the normal and flat-footed groups in either the agility variable (p = 0.141) or the vertical jump (p = 0.121). The conclusion of this study shows that there is no significant difference between regional level soccer players with normal and flat foot arch types in terms of agility and vertical jumping ability.